1998
DOI: 10.1093/bja/81.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic paravertebral block

Abstract: Paravertebral nerve block produces ipsilateral analgesia through injection of local anaesthetic alongside the vertebral column. It is advocated predominantly for unilateral surgery, for example, thoracotomy, chest wall trauma, breast surgery, cholecystectomy, herniorrhaphy or renal surgery, although it can be used as a bilateral technique. In chronic pain, it is used for the treatment of benign or malignant neuralgia. There is confusion over the indications for this block and it is apparent that much ignorance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
3
13

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(183 citation statements)
references
References 78 publications
(52 reference statements)
5
162
3
13
Order By: Relevance
“…3,8,18 Since we reported that the use of a blind technique led to a spray of dye anterior to the endothoracic fascia, at least as often as with the use of a neurostimulation approach, the difference between our results and those previously published may be attributed to differences in anthropometric characteristics of the patients included in these studies. on average, our patients had higher bMis compared to those subjects included in previously published studies.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…3,8,18 Since we reported that the use of a blind technique led to a spray of dye anterior to the endothoracic fascia, at least as often as with the use of a neurostimulation approach, the difference between our results and those previously published may be attributed to differences in anthropometric characteristics of the patients included in these studies. on average, our patients had higher bMis compared to those subjects included in previously published studies.…”
Section: Discussioncontrasting
confidence: 59%
“…8 This regional technique can also be used to provide unilateral somatic and sympathetic blocks, as required, for selected surgical procedures. 7,9,10 Additional postoperative benefits include a reduction in opioid requirements, earlier hospital discharge, 11 and a possible decreased risk for metastases and recurrence following surgery for breast cancer.…”
Section: Résultats : à L'exception De T5 Une Relation Linéaire a Pu mentioning
confidence: 99%
See 1 more Smart Citation
“…1,[4][5][6][7] It is noteworthy that, with blind techniques, the loss of resistance felt with paravertebral needle placement is much less definite than that with epidural insertion. 8 The advent of ultrasoundguided regional anesthesia has offered the potential to improve efficacy and safety via real-time visualization of the paravertebral space, the surrounding structures, and the approaching needle. 1 As such, ultrasound has been applied to the traditional paravertebral approaches in an effort to reduce the risk of pleural puncture as well as to ensure better delivery of medications into the paravertebral space.…”
Section: Résumémentioning
confidence: 99%
“…After collegial discussion, the theoretical positive ratio "analgesic advantage" against "infection risk" led the surgeon to accept the insertion of a catheter just below the surgical area. Consequently, because PV performance has been reported to be less risky in the anesthetized patient [11], we performed the PV block just after the surgery ended, when each patient had recovered efficient spontaneous breathing (e.g., respiratory rate >8 min…”
Section: Case Seriesmentioning
confidence: 99%